Janice VanCleave's the human body for every kid : easy activities that make learning science fun. - VanCleave, Janice Pratt (New York : J. Wiley, 1995)
Activities and scientific explanations help children learn about the parts of the human body and their functions.
Includes index.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
5.6.
5.6
Keywords: Human physiology -- Experiments -- Juvenile literature; Experiments; Human body -- Experiments; Human physiology -- Experiments; Human body -- Experiments; Physiology -- Experiments; Science -- Experiments